PEMEROLEHAN BAHASA DAN GANGGUAN BAHASA PADA ANAK USIA BATITA - Rina Devianty (JURNAL RAUDHAH, 2016)
The acquisition of the language for the children under three years is very important to be noticed, especially for the parents. This article tries to identify the language acquisition for the children early in order to the reader especially parents to have the basic knowledge in helping their children to get the speaking skill optimally. Then how to know and solve the speaking interference for the children.